Tracheostomy in infants: indications and outcomes - Sovtić, Aleksandar; Gojšina, Bojana; Baljošević, Ivan; Popović, Stefan (Vojnosanitetski pregled, 2024)
Background/Aim. Prolonged ventilation is the most common indication for pediatric tracheostomy. The aim of the study was to determine the indications, possible complications, and outcomes of tracheostomy in infants, as well as the association of patient phenotype with complications following tracheostomy. Methods. This retrospective study highlights the main indications, complications, and decannulation rates in tracheostomy pediatric patients treated at the Institute of Mother and Child Health Care of Serbia “Dr. Vukan Čupić”, Belgrade, for three years. Results. A total of 38 infants were included in our retrospective study, 31 (81%) of whom underwent elective tracheostomy, and 7 (19%) underwent urgent tracheostomy due to acute respiratory distress and difficult intubation. The mean age was 5.4 ± 3.5 months, and the youngest participant was 36 hrs old. The primary indication for elective tracheostomy was prolonged mechanical ventilation in 13 (42%) patients, neuromuscular disorders in 5 (16%), airway obstruction in 10 (32%), craniofacial anomalies in 2 (5%), and pulmonary disease in 1 (3%) patient. Early complications (occurring within the first seven days after tracheostomy) were present in 4 (10.5%) patients, three of whom had air leaks (due to inappropriate cannula selection), whereas wound dehiscence was reported in one patient. Late complications (those occurring more than seven days after tracheostomy) were reported in 4 (10.5%) patients and they were peristomal granulations in three patients and tube obstruction in one patient. There were no deaths associated with tracheostomy, although overall mortality was 21% (8 patents). All of these patients died as a result of their primary diseases. Seventeen (44%) patients were successfully decannulated. Conclusion. Most patients required long-term treatment and tracheostomy retention due to the nature of their primary diseases, which coincided with low decannulation rates. Therefore, tracheostomies should preferentially be carried out in specialized pediatric centers with trained medical personnel ensuring adequate health care.
Keywords: infant, newborn; respiration, artificial; serbia; tracheostomy.